The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.4300/jgme-d-13-00420.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Simulation-Based ACLS Education on Patient Outcomes: A Randomized, Controlled Pilot Study

Abstract: Background Simulation training is widely accepted as an effective teaching tool, especially for dealing with high-risk situations. Objective We assessed whether standardized, simulation-based advanced cardiac life support (ACLS) training improved performance in managing simulated and actual cardiac arrests. Methods A total of 103 second- and third-year intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…A recent study of simulation-based code training for physician team leaders found that it yielded no significant improvement in key processes of cardiac arrest care: time to initiation of CPR, time to administration of cardiac medication and time to defibrillation. 24 Yet, processes such as CPR initiation and defibrillator deployment rely on the actions of multiple providers, and they often unfold prior to the arrival of a physician leader. 25 The dynamic and unpredictable nature of response to cardiac arrest creates a tension between interdependence and the need for autonomous action within a diverse group of providers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study of simulation-based code training for physician team leaders found that it yielded no significant improvement in key processes of cardiac arrest care: time to initiation of CPR, time to administration of cardiac medication and time to defibrillation. 24 Yet, processes such as CPR initiation and defibrillator deployment rely on the actions of multiple providers, and they often unfold prior to the arrival of a physician leader. 25 The dynamic and unpredictable nature of response to cardiac arrest creates a tension between interdependence and the need for autonomous action within a diverse group of providers.…”
Section: Introductionmentioning
confidence: 99%
“…This study will follow a grounded theory approach in which the process of data collection and analysis occur simultaneously. 24 The approach allows for the pursuit of emergent themes through early data analysis, as well as the discovery of basic social processes within the data that may shape subsequent data collection. Grounded theory is an inductive process by which abstract categories are constructed to explain and synthesise data.…”
Section: Introductionmentioning
confidence: 99%
“…There is also literature that has shown no benefit to simulation training in resuscitation. A prospective study evaluating whether simulation-based ACLS training improves performance in managing simulated and actual cardiac arrest found no difference in adherence to the AHA guidelines 39. Another study evaluated whether participants who receive ACLS training on high-fidelity manikins performed better than those trained on low-fidelity manikins found no difference in groups on written tests scores 40.…”
Section: Discussionmentioning
confidence: 99%
“…A contribution to counteracting negative cultural traits within the OR may be made by increasing opportunities for positive practice and modeling of effective team-based competencies by students in an IPE setting [ 21 ]. There is increased emphasis on the need to produce “safe” practitioners in increasing numbers while, at the same time, there are increasing restrictions on practicing on real patients [ 22 ]. Simulation-based learning can help to overcome this problem by providing students with an opportunity to apply learned concepts and skills in a realistic clinical setting [ 8 , 23 ].…”
Section: Discussionmentioning
confidence: 99%